Anaerobic Reactors - Augustos de Lemos Chernicharo, Carlos (Biological Wastewater Treatment Series, 2007)
"Anaerobic Reactors is the forth volume in the series Biological Wastewater Treatment. The fundamentals of anaerobic treatment are presented in detail, including its applicability, microbiology, biochemistry and main reactor configurations. Two reactor types are analysed in more detail, namely anaerobic filters and especially UASB (upflow anaerobic sludge blanket) reactors. Particular attention is also devoted to the post-treatment of the effluents from the anaerobic reactors. The book presents in a clear and informative way the main concepts, working principles, expected removal efficiencies, design criteria, design examples, construction aspects and operational guidelines for anaerobic reactors. About the series: The series is based on a highly acclaimed set of best selling textbooks. This international version is comprised by six textbooks giving a state-of-the-art presentation of the science and technology of biological wastewater treatment. Other titles in the series are: Volume 1: Waste Stabilisation Ponds; Volume 2: Basic Principles of Wastewater Treatment; Volume 3: Waste Stabilization Ponds; Volume 5: Activated Sludge and Aerobic Biofilm Reactors; Volume 6: Sludge Treatment and Disposal"